Knockdown of Atg7 induces nuclear-LC3 dependent apoptosis and augments chemotherapy in colorectal cancer cells - Scherr, Anna-Lena; Jassowicz, Adam; Pató, Anna; Elßner, Christin; Ismail, Lars; Schmitt, Nathalie; Hoffmeister-Wittmann, Paula; Neukirch, Lasse; Gdynia, Georg; Goeppert, Benjamin; Schulze-Bergkamen, Henning; Jäger, Dirk; et al. (International journal of molecular sciences, 2020)
Autophagy is a catabolic process that enables cells to degrade obsolete content and refuel energy depots. In colorectal cancer (CRC) autophagy has been shown to promote tumorigenesis through energy delivery in the condition of uncontrolled proliferation. With this study, we aimed at evaluating whether autophagy sustains CRC cell viability and if it impacts therapy resistance. Initially, a colorectal cancer tissue micro array, containing mucosa (n = 10), adenoma (n = 18) and adenocarcinoma (n = 49) spots, was stained for expression of essential autophagy proteins LC3b, Atg7, p62 and Beclin-1. Subsequently, central autophagy proteins were downregulated in CRC cells using siRNA technology. Viability assays, flow cytometry and immunoblotting were performed and three-dimensional cell culture was utilized to study autophagy in a tissue mimicking environment. In our study we found an upregulation of Atg7 in CRC. Furthermore, we identified Atg7 as crucial factor within the autophagy network for CRC cell viability. Its disruption induced cell death via triggering apoptosis and in combination with conventional chemotherapy it exerted synergistic effects in inducing CRC cell death. Cell death was strictly dependent on nuclear LC3b, since simultaneous knockdown of Atg7 and LC3b completely restored viability. This study unravels a novel cell death preventing function of Atg7 in interaction with LC3b, thereby unmasking a promising therapeutic target in CRC.
Gesehen am 13.05.2020